Effectiveness of smart meter-based urban water loss assessment in a real network with synchronous and incomplete readings. (February 2019) - Bragalli, Cristiana; Neri, Mattia; Toth, Elena
Abstract: The availability of smart metered high-resolution water consumption data introduces, through the synchronous readings of the smart meters, new perspectives in the proactive approach to the monitoring of water losses. Measuring or transmission systems problems are unavoidable in real-world networks and, if not appropriately addressed, may compromise the ability to use smart meters to estimate water losses. The proposed Synchronous Water Balance methodology allows the near-real time assessment of water losses taking into account incomplete readings through a water consumption data validation and reconstruction model. The impact on water loss monitoring due to the lack of an increasing number of smart meters is investigated applying a random sampling and evaluating the corresponding error. The results, tested on a district of the city of Fano (Italy), suggest that the availability of near real-time synchronous water consumption measures can substantially improve the assessment of water losses in comparison to traditional approaches. Highlights: Smart metered high-resolution water consumption data for monitoring water losses. Synchronous Water Balance methodology for near-real time assessment of water loss. Validation of the methodology through comparison with Minimum Night Flow approach. Procedure for addressing presence of both unmetered users and missing readings. Stratified random sampling for assessing impact of temporarily unavailable meters.